ORGANIZATIONAL CULTURE, INNOVATION AND STRUCTURE AS DETERMINANTS OF ORGANIZATIONAL PERFORMANCE: A LITERATURE REVIEW - Iyer, Rama (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The purpose of this systematic literature review (SLR) is to investigate how organizational structure (OS), innovation and culture (OC) affect organizational performance (OP). With an emphasis on comprehending how these elements collectively affect performance results, it synthesizes previous research to investigate the direct and indirect relationships between OC, OS, and OP. Important factors like Organizational Quotient (OQ) are also thought to offer a thorough viewpoint. The review finds that OC, OS, and OP have beneficial relationships in a variety of scenarios, especially in small and medium-sized businesses (SMEs). This study aims to identify the ways in which organizational culture and structure influence performance and spur innovation in businesses by carefully examining previous studies.